Tectonic geomorphology of the Fox Peak and Forest Creek Faults, South Canterbury, New Zealand: slip rates, segmentation and earthquake magnitudes. Issue 4 (1st October 2016) - Stahl, T; Quigley, MC; Bebbington, MS
ABSTRACT: The Fox Peak and Forest Creek Faults in South Canterbury show evidence for segmentation based on the surface expression of late Quaternary faulting. Slip rates were calculated at over 100 sites along the Fox Peak Fault from (a) global positioning system (GPS) and total station fault scarp profiles; (b) field measurements of fault geometry and kinematics; and (c) age data from infrared stimulated luminescence, Schmidt hammer exposure-age dating and regional map correlations. Near the centre of fault segments, maximum slip rates for the Fox Peak Fault reach c. 1.6–1.7 mm yr −1, whereas an average slip rate of c. 1–1.5 mm yr −1 summed across the Forest Creek and Fox Peak Faults falls below rates derived by geodetic models. The geomorphology and single event displacements suggest segment-breaching ruptures of the Fox Peak Fault during late Quaternary earthquakes with moment magnitudes ( M W ) of 7.0–7.2. This study highlights the role that evaluations of landscape evolution in reverse faulting regimes can play in assessing seismic hazard.